The Effect of Gambir Leaves on Cholesterol Levels in Bangka Regency - Muhamad Seto Sudirman; Eva Dewi R Purba; Auronita Puspa Pratiwi (PT FORMOSA CENDEKIA GLOBAL, 2023)
People in the Province of Bangka Belitung Islands are still using medicinal plants inherited from their ancestors, especially in rural areas that are still far from the reach of health facilities organized by the government as a promotional, preventive and curative effort in overcoming health problems. Gambir leaves are a medicinal plant used to lower blood sugar levels which are used by ethnic Malays in the province of Bangka Belitung Islands. As to achieve the goal of the use of traditional medicine for public health, scientific evidence of quality, safety and efficacy is needed. How is the effectiveness of gambier leaves as a traditional medicine to lower blood sugar in ethnic Malays in the Province of Bangka Belitung Islands. Observe the clinical effectiveness (effectiveness) of the use of gambir leaf boiled water as a traditional medicine to lower blood sugar and determine the safety of the liver and kidneys of ethnic Malays in the Province of Bangka Belitung Islands. Development of a study of traditional medicine formularies used in patients with hyperglycemia disorders and found natural medicinal ingredients to be the most effective and without side effects on the liver and kidneys